FAKTOR-FAKTOR YANG MEMPENGARUHI ADOPTION E-PAYMENTTERHADAP GENERASI Z PENGGUNA GOPAYDI JAKARTA BARAT - AUDREY DEANA SHAFIRA; MUWAFICK HIDAYAT (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
The purpose of this study is to identify and analyze the influence of Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), Facilitating Conditions (FI), Government Support (GS), and Quality of Internet (QI) on the Adoption of e-payment (IA) among GoPay users, specifically Generation Z, in West Jakarta. This research employs a descriptive and causal research design, using a likert scale with five measurement points. The sampling method used is Purposive Sampling, with a total of 210 respondents. The data analysis methods employed include Structural Equation Modeling (SEM) using SmartPLS 4.0 as the analytical tool. The results of this study indicate that the Performance Expectancy, Effort Expectancy, Social Influence, Facilitating, Government Support have a positive influence on the Adoption of e-payment. However, the variable Quality of Internet has no influence on the variable Adoption of e-payment.